Case Report: Tuberous sclerosis complex-associated hemihypertrophy successfully treated with mTOR inhibitor sirolimus - Konomi Shimoda; Konomi Shimoda; Hiroyuki Iwasaki; Yoko Mizuno; Masafumi Seki; Masakazu Mimaki; Motohiro Kato; Aya Shinozaki-Ushiku; Harushi Mori; Seishi Ogawa; Seishi Ogawa; Masashi Mizuguchi; et al. (Frontiers Media S.A., 2024)
Tuberous sclerosis complex (TSC) is an autosomal dominant disorder caused by a mutation in either of the two tumor suppressor genes, TSC1 and TSC2. Due to dysregulated activity of the mammalian target of rapamycin (mTOR) pathway, hamartomas or benign tumors frequently occur in many organs and are often treated with mTOR inhibitors. Hemihypertrophy is a rare complication of TSC. Although not being a tumor, progressive overgrowth of the affected limb may cause cosmetic and functional problems, for which the efficacy of mTOR inhibitors has not been reported previously. We herein report a case of TSC-associated hemihypertrophy. In this case, genetic studies revealed TSC1 loss of heterozygosity as the cause of hemihypertrophy. Clinically, pharmacological treatment with an mTOR inhibitor sirolimus successfully ameliorated cosmetic and functional problems with no intolerable adverse effects.